Molecular mechanisms underlying the regulation of tobacco defenses against Bemisia tabaci by the salivary effector BtArmet targeting NtWRKY51 - DU Hui; WANG Xiaowei; LIU Shusheng (浙江大学学报. 农业与生命科学版)
The whitefly Bemisia tabaci, an important agricultural insect pest, secretes saliva into plants while feeding on them. Our previous study found that the whitefly secretes the salivary effector protein BtArmet (Bemisia tabaci arginine rich, mutated in early stage of tumors) to inhibit plant resistance by targeting tobacco cystatin. In this study, we continued to screen tobacco proteins that interact with the salivary effector protein BtArmet. Yeast two-hybrid and bimolecular fluorescence complementation (BiFC) assays showed that Nicotiana tabacum WRKY51 interacted with BtArmet. The up-regulation of NtWRKY51 gene in tobacco was significantly induced by whitefly infestation. However, virus-induced gene silencing (VIGS) assays combined with bioassay of whiteflies showed that the fecundity of NtWRKY51-silenced tobacco plants by female whiteflies was significantly lower than that of the negative control (tobacco with silenced empty vector). Silencing NtWRKY51 gene had no effect on phytohormone signaling pathways mediated by salicylic acid or jasmonic acid in tobacco plants. These results provide references for further investigations on the molecular mechanisms underlying plant resistance to whiteflies.